Opções reais em decisões de investimento de exploração e produção - Scartezini, André Avila (2006)
This work reviews the main concepts of real option theory. It intends to discuss the investment decision problem under uncertainty in petroleum Exploration and Production (E&P). Simple models including the classic Padock, Siegel and Smith (1998) were focused because they may be easily implemented in petroleum companies. All the models discussed consider the Geometric Brownian Motion (GBM) which may be a reasonable approach to modeling prices since appropriated parameters are considered. In particular, a compound option model to exploration and development is presented. It reveals to be more appropriated, mainly when considering both the geologic risk and stages with distinct expiration dates. The selection of projects with real options is also tested in a representative portfolio of development projects, which results in an increasing NPV-investment ratio of selected portfolio.